Sexualidade e escolha de objeto na teoria psicanalítica freudiana e nas teorias biológicas do comportamento humano - Guarnieri, Silvana (2014)
Although the relationship between psychoanalysis and biology has been denied by many Freudian followers, today much study has been done in Freud's work, resuming his concepts within the naturalistic bias. Aiming to deepen these relationships, this study aims to analyze the convergences between the psychoanalytic concept of object choice and sociobiological studies regarding choice of partners. For psychoanalysis, human sexuality doesn´t have a main objective to reproduce, but this does not take us away from biological conceptions of sexuality, as is pointed out by several theoretical biology and contrary to a widespread view within the psychoanalytic means. It is thus to analyze how psychoanalysis and biology study this aspect of human sexual behavior, including their specificities, but also looking to evaluate their degree of convergence and complementarity that can then establish